2021
DOI: 10.1002/job.2516
|View full text |Cite
|
Sign up to set email alerts
|

Thinking of you thinking of me: An integrative review of meta‐perception in the workplace

Abstract: Decades of research demonstrate a fundamental human tendency to care about how one is seen by others, and for good reason; the perceptions and appraisals of others affect a wealth of important outcomes in our lives. In the workplace, for example, these outcomes include dismissals, bonuses, and promotions. In this review, we integrate a diverse body of research surrounding human "beliefs about how we are seen by others" and define these beliefs as meta-perceptions. We derive an overarching framework to highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 95 publications
(191 reference statements)
0
25
0
Order By: Relevance
“…For example, in the aforementioned studies (Ramsey et al, 2017; Ramsey & Hoyt, 2015), women were asked to evaluate the extent to which their partner surveyed their bodies and tested the relationship of such perceptions with women's self‐objectification. On the one hand, meta‐perceptions are important indicators of one's attitudes and behaviours (e.g., Grutterink & Meister, 2021; Pavetich & Stathi, 2021); on the other hand, however, they are likely affected by a priori attitudes toward their partner, cognitive biases or self‐enhancement motives (e.g., Sedikides & Gregg, 2008) and, thus, they cannot be considered as a fully reliable indicator of partner's tendency to objectify.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the aforementioned studies (Ramsey et al, 2017; Ramsey & Hoyt, 2015), women were asked to evaluate the extent to which their partner surveyed their bodies and tested the relationship of such perceptions with women's self‐objectification. On the one hand, meta‐perceptions are important indicators of one's attitudes and behaviours (e.g., Grutterink & Meister, 2021; Pavetich & Stathi, 2021); on the other hand, however, they are likely affected by a priori attitudes toward their partner, cognitive biases or self‐enhancement motives (e.g., Sedikides & Gregg, 2008) and, thus, they cannot be considered as a fully reliable indicator of partner's tendency to objectify.…”
Section: Introductionmentioning
confidence: 99%
“…Although research has shown that self-awareness can predict important outcomes such as job-performance ratings, most of this work has operationalized self-awareness as differences, or a lack thereof, between self-report and other-ratings on constructs such as job performance and leadership behaviors or style (e.g., Atwater & Yammarino, 1992; Fleenor et al., 2010; Fletcher & Baldry, 2000). In contrast, research using metaperceptions has focused on awareness of one’s reputation, operationalized as differences between metaperceptions and other-ratings (Foster & Stone, 2021) and interpersonal relations (Grutterink & Meister, 2022). In other words, the more accurately someone can predict ratings from others, the higher their self-awareness.…”
Section: The Value Of Multiple Perspectivesmentioning
confidence: 99%
“…Foster and Stone (2021) found that metaperceptions of conscientiousness predicted task performance, organizational-citizenship behaviors, and counterproductive work behaviors above and beyond traditional self-report ratings. And a recent meta-analysis (Grutterink & Meister, 2022) found that research in sport psychology and organizational behavior indicates metaperceptions can enhance task performance and creativity. Grutterink and Meister(2022) concluded, "Metaperceptions can have important implications for employees' affect, cognition, and behavior, yet there is a lack of research exploring metaperceptions in work settings" (p. 1).…”
Section: Metaperceptionsmentioning
confidence: 99%
“…, a question we term meta-affordance. That is, just as meta-perceptions are beliefs about how others perceive the self(Grutterink & Meister, 2021;Kenny, 1994), we propose meta-affordances are beliefs about what others expect from oneself. As with affordances, we propose that assessments of meta-affordances posit not only what goal(s) others hold, but also how they are expected to behave to facilitate those goals.…”
mentioning
confidence: 95%